'BEAMED DIRECTLY TO THE CHILDREN': SCHOOL BROADCASTING AND SEX EDUCATION IN BRITAIN IN THE 1960s AND 1970s. (8th September 2015) - Gregory, Mara
ABSTRACT: This paper presents findings from a larger research project that addresses the production, content and reception of sex education broadcasts produced by the British Broadcasting Corporation and Independent Television in the 1960s and 1970s. More than educational aids, these programmes were vehicles of communication with explicit and implicit messages regarding sexual morality and the nature of childhood. With a focus on the broadcast media and their modes of address to children, this paper connects sex education content with classroom practice and broadly questions how broadcasts portrayed and authorised certain images, types of knowledge and methods for teaching children about sex.